PERANAN DAN KONTRIBUSI MAJELIS DIKDASMEN PCM MEDAN DELI DALAM PENINGKATAN KUALITAS PENDIDIKAN MUHAMMADIYAH - Fadillah, Fajar; Qorib, Muhammad; Zailani, Zailani (CV. Lafadz Jaya, 2025)
(Dikdasmen) PCM Medan Deli in enhancing the quality of Muhammadiyah education. It focuses on assessing the extent to which the Majelis Dikdasmen PCM Medan Deli has fulfilled its tasks and functions, which are vital for supporting Muhammadiyah’s educational goals. The research employs a qualitative approach, particularly using ethnographic methods to understand the practices and contributions of the Majelis. Data was collected through observation, interviews with the chairman of Majelis Dikdasmen PCM Medan Deli, and analysis of documents related to educational practices. The results show that the Majelis has made significant contributions in various areas: providing educational facilities, improving teacher quality, and implementing regular evaluations of educational processes. These actions have fostered a synergy between schools and the Majelis, which has contributed to the growth of Muhammadiyah schools in Medan Deli. This research emphasizes the importance of collaboration between the Majelis and schools in fulfilling Muhammadiyah's vision to create a society based on Islamic values and principles.